PWE-005 Vedolizumab dose escalation as a way of recapturing response in patients with inflammatory bowel disease. (8th June 2018) - Birdi, S; Sierra Morales, M; Samaan, MA; Brown-Clarke, C; Stanton, A; Ray, S; Koumoutsos, I; Mawdsley, J; Anderson, S; Sandersdon,; Irving, PM
Abstract : Introduction: Increasing vedolizumab (VDZ) dosing frequency to recapture response has been shown to be effective in clinical trials but there is limited real-life data from the clinical practice. In this study we assessed whether VDZ dose escalation helped recapture response in a large cohort of patients in a tertiary referral IBD centre. Methods: A retrospective cohort study was performed by reviewing prospectively recorded clinical data for patients who received VDZ between November 2014 and October 2017. Patients who had sub-optimal response and had been escalated to 6 or 4 weekly infusions were identified. Data collected for demographics, previous biologic exposure, concomitant immunomodulators (IM), steroid use (SU), clinical disease activity for CD (HBI) and UC (SCCAI), and CRP levels at baseline, 12 and 24 weeks after dose escalation. Of the total 139 patients on VDZ, 36 (27%) had been escalated to Q4 (30) or Q6 (6), of whom 5 were further escalated to Q4 (72% male, median age 44, previous biologics exposure 81%, 49% concomitant IM and 16% SU at time of escalation). 18 patients had CD (50%), 14 UC (39%), and 4 (11%) IBD-U which were included in the UC group for the purpose of analysis. Duration of VDZ before and after dose escalation with a median of 7 m (ranges 0–22, 2–25 respectively). Currently 76% remain on VDZ after dose escalation (median 7 m after escalation). Clinical response was defined as HBI or SCCAI reduction >3. Remission as HBI <5 or SCCAI <3. Paired HBI, SCCAI, CRP values at baseline, week 12 and 24 were compared using Wilcoxon signed-rank test Results: Patients with CD had a median HBI of 4 (range 0–27), 4 (0–29) and 3 (0–8), at baseline, 12 and 24 weeks. In UC group, the median SCCAI was 6 (range 0–11); 4.5 (1–11), and 4 (0–10), at baseline, 12 and 24 weeks. CRP for both groups at baseline was a median of 6 (1–23), 5 (1–46) at w12, and 2 (1–17) at w24. HBI and SCCAI at baseline, 12 and 24 weeks after dose escalation Statistically significant differences were noted in the UC group between SCCAI at baseline and after 24 weeks (p 0.01) and overall CRP at baseline and 24 w (p 0.04). Of all patients with clinically active disease at baseline (n=20), 5 achieved clinical response (25%), an additional 4 achieved clinical remission (20%). Conclusions: In a real life setting, increasing dosing frequency in patients with sub-optimal response to VDZ is effective in approximately half of patients and should be considered as an intervention.